Pengaruh Komunikasi dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Dinas Kelautan dan Perikanan Kabupaten Bima - Rahman, Arif; Aprianti, Kartin; Rahmatia, Rahmatia (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of communication and work environment on employee morale at the Maritime Affairs and Fisheries Service of Bima Regency. A quantitative approach was employed using a Likert-scale questionnaire distributed to 80 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS for Windows. The results reveal that communication (β = 0.551; t = 18.459; p < 0.05) and work environment (β = 0.401; t = 16.786; p < 0.05) have a significant partial effect on employee morale. Simultaneously, these two variables contribute 94.4% to the increase in employee morale (R² = 0.944; F = 43.288; p < 0.05). These findings indicate that effective communication and a supportive work environment can enhance motivation and productivity among public sector employees. The practical implication of this study suggests that organizational management needs to improve the quality of internal communication and create a conducive work environment to optimize organizational performance.